2003
DOI: 10.2106/00004623-200305000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Intradiscal Spine Fusion Using a Minimally Invasive Gene-Therapy Technique

Abstract: Kyongtae T.; and Avioli, Louis V., ,"Thoracoscopic intradiscal spine fusion using a minimally invasive gene-therapy technique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 16 publications
(23 reference statements)
1
15
0
3
Order By: Relevance
“…Together with studies from other research groups using adenovirus, retrovirus and nonviral vectors [Mason et al, 1998;Lieberman et al, 1999;Baltzer et al, 2000;Okubo et al, 2000;Laurencin et al, 2001;Riew et al, 2003], they provide strong evidence for the feasibility of this approach as a clinical alternative to BMP protein therapy. In related studies, one of us (RBR) showed that AdCMV-BMP7 transduction of tooth pulp can stimulate regeneration of a dentin-like mineralized matrix in vivo [Rutherford, 2001].…”
Section: Use Of Adcmv-bmp7 For Regeneration Of Cranial and Long Bone mentioning
confidence: 81%
“…Together with studies from other research groups using adenovirus, retrovirus and nonviral vectors [Mason et al, 1998;Lieberman et al, 1999;Baltzer et al, 2000;Okubo et al, 2000;Laurencin et al, 2001;Riew et al, 2003], they provide strong evidence for the feasibility of this approach as a clinical alternative to BMP protein therapy. In related studies, one of us (RBR) showed that AdCMV-BMP7 transduction of tooth pulp can stimulate regeneration of a dentin-like mineralized matrix in vivo [Rutherford, 2001].…”
Section: Use Of Adcmv-bmp7 For Regeneration Of Cranial and Long Bone mentioning
confidence: 81%
“…Cells were then incubated overnight with AdBMP-2. Anterior arthrodesis was performed by a thoracoscopic technique and the researchers reported a 100% fusion rate by histologic and radiologic evaluation for six of six disc spaces treated with AdBMP-2, whereas none of the controls fused (Riew et al, 2003). Wang et al compared single-level posterolateral spine fusion rates between rhBMP-2 with various carriers, bone marrow cells transduced for 48 hours with AdBMP-2 and iliac crest bone graft (ICBG) in rats.…”
Section: Cells Combined With Ex Vivo Gene Therapymentioning
confidence: 99%
“…BMP-2, approved by Food and Drug Administration (FDA) for clinical practice, is the most potent member in promoting bone and cartilage development and therefore wins a popular choice for MSCs-based BTE (Lieberman et al, 1998;Lieberman et al, 1999;Lou et al, 1999;Turgeman et al, 2001;Olmsted-Davis et al, 2002;Blum et al, 2003;Gugala et al, 2003;Park et al, 2003;Riew et al, 2003;Tsuda et al, 2003;Kumar et al, 2004;Hasharoni et al, 2005;Egermann et al, 2006;Feeley et al, 2006). The BMP-2-modified MSCs are proven to increase the alkaline phosphatase (ALP) activity, mineralization, and cell proliferation in vitro and induce ectopic bone formation, heal critical size bone defect, repair fracture, and trigger spinal fusion in vivo (Lou et al, 1999;Moutsatsos et al, 2001;Turgeman et al, 2001;Blum et al, 2003;Park et al, 2003;Riew et al, 2003;Tsuda et al, 2003;Hasharoni et al, 2005;Egermann et al, 2006;Feeley et al, 2006). BMP-7 plays a key role in osteoblast differentiation, and there is only one study in which MSCs are engineered with BMP-7.…”
Section: Applicable Genes For Mscs Modificationmentioning
confidence: 99%
“…Adenovirus vector is one of the most popular vectors for MSC gene therapy aimed at BTE Dumont et al, 2002;Olmsted-Davis et al, 2002;Blum et al, 2003;Dayoub et al, 2003;Gugala et al, 2003;Li et al, 2003;Park et al, 2003;Riew et al, 2003;Sugiyama et al, 2003;Tsuda et al, 2003;Yang et al, 2003;Kumar et al, 2004;Zheng et al, 2004;Zhao et al, 2005;Egermann et al, 2006;Feeley et al, 2006;Zachos et al, 2006). Adenovirus vector is characterized by efficient transduction of quiescent cells and a relatively high capacity for transgene insertion.…”
Section: Selection Of Vectorsmentioning
confidence: 99%